Formal Semantics of Dynamic Constraints and Derivation Rules in ORM - Balsters, Herman; Halpin, Terry (IGI Global, 2016)
This paper provides formal semantics for an extension of the Object-Role Modeling approach to support declaration of dynamic rules. Dynamic rules differ from static rules by involving state transitions, rather than simply individual states. This paper restricts application of dynamic rules to single-step transactions, with a previous state (input to the transaction) and a new state (the result of that transaction). These dynamic rules specify an elementary transaction type by indicating which kinds of objects or facts (being added, deleted or updated) are involved. Dynamic rules may declare pre-conditions relevant to the transaction, and a post-condition stating the properties of the new state. In this paper the authors provide such dynamic rules with a formal semantics based on sorted, first-order predicate logic. The key idea underlying their solution is the formalization of dynamic constraints in terms of static constraints on the database transaction history.